Television as theatre text in the austere academy: a curricular exploration. Issue 3 (3rd July 2019) - Miller, Hillary
ABSTRACT: The theatre classroom is necessarily a space in dialogue with myths about the marginalisation of theatre as an art and theatre audiences as a public. It is precisely because theatre is a marginalised discipline that curricula should incorporate the processes by which the labour of theatre artists changes value and joins the mainstream; playwrights employed in television offer a relevant study of just that. How do we revise undergraduate curricula in order to substantially address this intermediality in a way that is legible for students? And where do television and theatre meet in existing theatre courses and objectives?